Assessment of diagnosis of inflammatory breast cancer cases at two cancer centers in Egypt and Tunisia. (24th January 2013) - Schairer, Catherine; Soliman, Amr S.; Omar, Sherif; Khaled, Hussein; Eissa, Saad; Ayed, Farhat Ben; Khalafallah, Samir; Ayoub, Wided Ben; Kantor, Elizabeth D.; Merajver, Sofia; Swain, Sandra M.; Gail, Mitchell; et al.
Abstract The diagnosis of inflammatory breast cancer (IBC) is largely clinical and therefore inherently somewhat subjective. The objective of this study was to evaluate the diagnosis of IBC at two centers in North Africa where a higher proportion of breast cancer is diagnosed as IBC than in the United States (U.S.). Physicians prospectively enrolled suspected IBC cases at the National Cancer Institute (NCI) – Cairo, Egypt, and the Institut Salah Azaiz (ISA), Tunisia, recorded extent and duration of signs/symptoms of IBC on standardized forms, and took digital photographs of the breast. After second‐level review at study hospitals, photographs and clinical information for confirmed IBC cases were reviewed by two U.S. oncologists. We calculated percent agreement between study hospital and U.S. oncologist diagnoses. Among cases confirmed by at least one U.S. oncologist, we calculated median extent and duration of signs and Spearman correlations. At least one U.S. oncologist confirmed the IBC diagnosis for 69% (39/50) of cases with photographs at the NCI‐Cairo and 88% (21/24) of cases at the ISA. All confirmed cases had at least one sign of IBC (erythema, edema, peau d'orange) that covered at least one‐third of the breast. The median duration of signs ranged from 1 to 3 months; extent and duration of signs were not statistically significantly correlated. From the above‐mentioned outcomes, it can be concluded that the diagnosis of a substantial proportion of IBC cases is unambiguous, but a subset is difficult to distinguish from other types of locally advanced breast cancer. Among confirmed cases, the extent of signs was not related to delay in diagnosis.